2007
DOI: 10.1063/1.2821298
|View full text |Cite
|
Sign up to set email alerts
|

Lessons about likelihood functions from nuclear physics

Abstract: Abstract. Least-squares data analysis is based on the assumption that the normal (Gaussian) distribution appropriately characterizes the likelihood, that is, the conditional probability of each measurement d, given a measured quantity y, p (d | y). On the other hand, there is ample evidence in nuclear physics of significant disagreements among measurements, which are inconsistent with the normal distribution, given their stated uncertainties. In this study the histories of 99 measurements of the lifetimes of f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The results of this study agree with earlier research that also observed Student-t tails, but only looked at a handful of subatomic or astrophysics quantities up to z ∼ 5 − 10 [16,19,[56][57][58]. Unsurprisingly, the tails reported here are mostly heavier than those reported for repeated measurements made with the same instrument (ν ∼ 3−9) [59][60][61], which should be closer to Normal since they are not independent and share most systematic effects.…”
Section: A Comparison With Earlier Studiessupporting
confidence: 90%
See 3 more Smart Citations
“…The results of this study agree with earlier research that also observed Student-t tails, but only looked at a handful of subatomic or astrophysics quantities up to z ∼ 5 − 10 [16,19,[56][57][58]. Unsurprisingly, the tails reported here are mostly heavier than those reported for repeated measurements made with the same instrument (ν ∼ 3−9) [59][60][61], which should be closer to Normal since they are not independent and share most systematic effects.…”
Section: A Comparison With Earlier Studiessupporting
confidence: 90%
“…Modelling the heavy tails may help us understand the observed distributions. One way is to assume that the measurement values are normally distributed with standard deviation t that is unknown but which has a probability distribution f (t) [15,[17][18][19]77]. The measured value x is then expected to have a probability distribution…”
Section: Modellingmentioning
confidence: 99%
See 2 more Smart Citations